2022
DOI: 10.1038/s41591-022-02074-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of Aβ42/40, p-tau231 and p-tau217 for Alzheimer’s trial selection and disease monitoring

Abstract: Blood biomarkers indicative of Alzheimer’s disease (AD) pathology are altered in both preclinical and symptomatic stages of the disease. Distinctive biomarkers may be optimal for the identification of AD pathology or monitoring of disease progression. Blood biomarkers that correlate with changes in cognition and atrophy during the course of the disease could be used in clinical trials to identify successful interventions and thereby accelerate the development of efficient therapies. When disease-modifying trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
146
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 56 publications
17
146
0
Order By: Relevance
“…Our Aβ ସଶ /Aβ ସ AUC is consistent with the AUC reported in other studies of cognitively normal individuals based on Simoa immunoassays [15,33]. Our findings also corroborate previous studies indicating that plasma p-tau measures more closely reflect brain amyloid levels compared to plasma measures of amyloid [16] and that p-tau231 has the highest AUC at the preclinical stage [14][15][16]. As expected, based on our univariate results, plasma p-tau, specifically p-tau231, and Aβ measures were the most important variables in the best multivariate classifier, which outperformed univariate classifiers and had a sensitivity and specificity of about 80% at its optimal operating point.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our Aβ ସଶ /Aβ ସ AUC is consistent with the AUC reported in other studies of cognitively normal individuals based on Simoa immunoassays [15,33]. Our findings also corroborate previous studies indicating that plasma p-tau measures more closely reflect brain amyloid levels compared to plasma measures of amyloid [16] and that p-tau231 has the highest AUC at the preclinical stage [14][15][16]. As expected, based on our univariate results, plasma p-tau, specifically p-tau231, and Aβ measures were the most important variables in the best multivariate classifier, which outperformed univariate classifiers and had a sensitivity and specificity of about 80% at its optimal operating point.…”
Section: Discussionsupporting
confidence: 91%
“…In a cohort that included individuals with and without cognitive impairment, Rauchmann et al examined trajectories of plasma p-tau181 and NfL relative to cerebrospinal fluid or imaging measure-based definitions of amyloid (A), tau (T), and neurodegeneration (N) status and found that relative to the A−TN− group, all other groups exhibited steeper longitudinal increases in NfL [13]. Further, recent cross-sectional and longitudinal studies have shown early changes of all plasma biomarkers but note that p-tau231 changes earliest in response to Aβ deposition [1416]. These findings suggest that these plasma biomarkers may be dynamic in the preclinical phase of AD and even earlier.…”
Section: Introductionmentioning
confidence: 99%
“…This further emphasizes the value of plasma GFAP in uncovering AD-related neuropathological changes. As a growing number of studies demonstrated the great promise of plasma p-tau231 and p-tau217 in the early identification of AD pathophysiology [ 12 , 21 23 ], their inclusion in the analysis may yield intriguing results. However, limited by the current technical conditions, we are unable to quantify their concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the previously reported dynamics across the clinical spectrum of AD [ 19 ] and the comparable concentrations of plasma Aβ in AD and controls [ 43 ], supporting that plasma Aβ levels might reflect peripheral Aβ generation more than they reflect AD brain pathology [ 19 ]. However, other studies demonstrated the potential of plasma Aβ markers in capturing early cerebral Aβ changes [ 10 , 22 , 23 ]. With the development of technology, recent studies have revealed that mass spectrometry-based methods outperform most immunoassays in the precise assays of plasma Aβ [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation